Production of G0 potato seeds from in vitro cultured plantlets - Jajang Supriatna; Lisma Sabilah (Universitas Muhammadiyah Magelang, 2024)
Good quality seeds are needed to produce potato tubers that have high quantity and quality. Seed availability needs to be supported by propagation techniques through in vitro culture. The purpose of this technical note is to provide information regarding the production stages of G0 potato seeds from in vitro cultured plantlets. Data searches were carried out from January 23 to February 24 2023 at CV. Bumi Agro Technology, Kertawangi Village, Cisarua District, Kabupaten Bandung Barat. Data was obtained from observations, field practice, discussions and interviews, as well as literature studies. The results of the data search obtained information on the production stages of G0 potato seeds, which consist of : management of plantlets originating from the IPB PPSHB Laboratory, acclimatization, transplanting, mini cuttings, land preparation, transplanting mini cuttings, maintenance including fertilizing, watering, replanting, controlling plant pest organisms, as well as harvesting and post-harvest. The results of these stages produce G0 potato seeds which are ready to be planted to produce G1 potato tubers or used as a source of explants in in vitro culture.